Creative Thinking Ability of Visual-Dominant and Visual-Kinesthetic Students in Solving Statistics Problems - Fadlilah, Chusnul; Karim, Karim; Hartono, Sugi (Journal of Mathematical Pedagogy (JoMP), 2021)
Creative thinking ability is a personal ability to carry out mental activities to produce an innovative new product. This study aims to analyze the level of creative thinking ability (LCT) of students with visual-dominant and visual-kinesthetic learning styles in solving statistics problems. Participants of this qualitative research are two junior high school students in 8th grade. The participant selection using purposive sampling technique, namely subjects who have a visual-dominant and visual-kinesthetic learning style. The instrument consisted of a learning styles questionnaire, the statistical problem-solving test, and task-based interviews. The indicators used to assess creative thinking products include fluency, flexibility, and originality. The data collected to be analyzed using the data source triangulation technique (reducing, presenting, verifying, and conclusions). The results showed that students who had a visual-dominant learning style met the indicators of fluency and originality. So, he was categorized at LCT 3 (creative). Meanwhile, students who have a visual-kinesthetic learning style only meet fluency indicators, so he was categorized at LCT 1 (almost not creative).